World Editors Dynamics of Global Publishing and the Latin American Case between the Archive and the Digital Age - Guerrero, Gustavo; Loy, Benjamin; Müller, Gesine (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2020)
The existence of World Literature depends on specific processes, institutions, and actors involved in the global circulation of literary works. Looking at Latin American 20th and 21st century literatures, this book analyzes the role of publishing houses, politics of translation, mediators and gatekeepers, to provide insights into the processes that enable books to cross borders and to be transformed into globally circulating commodities.